Desain Majalah Penunjang Promosi Dan Informasi Pada SMK Karya Bangsa Kota Tangerang - Dian Sugiarto; Suhadi Suhadi (UNIVERSITAS RAHARJA, 2019)
The development of information technology is very advanced. Information Plays an important role, with information makes it easir for people to find information they want, information can be obtained through print and electronic media, especially print media shaped magazine design in this case the SMK Karya Bangsa The City Of Tangerang very requires media magazines to easily load the entire information. Therefore the author made a magazine media at the SMK Karya Bangsa The City Of Tangerang so that the information easily known and the promotion system becomes more effective and creative is expected to be improve the image and improve marketing at school. Methodology used in this study include problem analysis methods, methods data collection, design analysis methods and design concept methods include : media planning, message planning and visual planing. In order to produce a design the good media for this magazine is using design support software like Adobe Photoshop CS5 and Adobe InDesign CS5, therefore the authors do the design mgazine media summarized in this chapter with the title “ DESIGN VISUAL COMUNICATION MEDIA FROM OF MAGAZINE DESIGN AS SUPPORTING PROMOTION AND INFORMATION ON SMK KARYA BANGSA THE CITY OF TANGERANG”.